(untitled) (KYAMC Journal, 2020)
Background. In developing countries, inadequate knowledge and cultural practice on complementary feeding (CF) is one of the main reasons for malnutrition. Objective: This study aimed to document the knowledge, attitude, and practices pertaining to CF among the mothers of rural area in Bangladesh. Materials and Methods: A communitybased cross-sectional study was conducted in upazila health complex, kachua, Chandpur from July to December, 2017. A total 408 mothers of the babies aged 6-24 months and children under six months were included. Data were collected from the mothers/caregivers of the children in a pretested semi-structured data collection sheet and analyzed by SPSS version 20. Appropriate statistical tests were done. Statistical significance was considered if p value was <0.05. Results: Knowledge regarding recommended CF practice only 50.8% but feeding should be started at 6 months of age (52.9),thick consistency (40.2%), adequate quantity( 61.8%), and appropriate quality (62.3%) cases. Knowledge in recommended appropriate timing and consistency varied significantly with maternal education. Frequency of CF was not appropriate in many cases. Most common first complimentary food was thick dal with rice/roti, khichuri rice 166(40.7%). One hundred twenty four (30.4%) mothers did not properly clean their hands before feeding and 138(33.8%) of mother used bottle for feeding, force full feeding (56.9%) and environment during feeding playing 72.5% and roaming around 25.5%. Conclusion: CF knowledge and practices are far gap from ideal in our country. Awareness building in the community may change improper feeding practices need health education. KYAMC Journal Vol. 11, No.-1, April 2020, Page 26-31